PEMANFAATAN PERPUSTAKAAN MINI UNTUK MENINGKATKAN MINAT BACA MASYARAKAT KELURAHAN TALANG PUTRI KECAMATAN PLAJU - Sunardi, Sunardi; Mahrom DS, Yudha; Gusmiatun, Gusmiatun; Agusria, Lesi; Afrida, Anggrelia; Hari, Kurnia Krisna; Sarwandy, Agung; Sahri, Yulian (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The existence of a mini library in Talang Putri Plaju Village, is very attractive, with a beautiful environment but very few visitors. This is because the administration and environmental conditions of the library are not well organized. The purpose of this service activity is to optimize the benefits of the Taman Edukasi mini library to increase public interest in reading in Talang Putri Village. The method used is counseling to the community and direct assistance to library managers. The time required to complete the activity is one month. The results of the activity show that to increase people's reading interest, it can be done through administrative arrangements, library layout arrangements, outdoor arrangements, and increasing the number of book collections. Some things that can be done are: 1) Make a list of book collections, guest lists, catalogs and visitor rules. 2) Arrange the layout (layout) of books and the correct placement of bookshelves. 3) Arrange a comfortable outdoor environment for readers, and 4) Collaborate with several parties to add to the book collection. The results of the evaluation after one month of service activities are the increasing number of visitors per week, reaching 31 people.